Efek Perbandingan Sosial terhadap Ketidakpuasan Tubuh di Kalangan Remaja Perempuan Pengguna Instagram - Sausan Thifaal Atiqah; Arie Gunawan H Zubair; Tarmizi Thalib (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This study aims to determine the effect of social comparison on body dissatisfaction among female adolescents who use Instagram. Social comparison refers to the process in which individuals compare themselves to others in terms of physical appearance, while body dissatisfaction refers to the feeling of being unhappy with one’s body or physical appearance. This study used a quantitative method with a survey involving 385 female adolescents aged 18-22 who actively use Instagram. Data were collected using validated scales for body dissatisfaction and social comparison. Regression analysis results showed a significant relationship between social comparison and body dissatisfaction, with an F-value of 4.378 and a significance of 0.037. The R-Square value of 0.011 indicates that social comparison explains only 11% of the variance in body dissatisfaction. These results suggest that the more frequently adolescents engage in social comparison on Instagram, the higher their levels of body dissatisfaction. Therefore, the use of social media, especially Instagram, can exacerbate negative body perceptions among female adolescents, ultimately having a detrimental impact on mental health. Interventions are needed to reduce harmful social comparisons and promote self-acceptance.